Berlitz Arabian CD pack (Berlitz / APA, 2003)
This CD contains eight topics to help in learning Arabic, starting from basic Arabic expressions, and includes more than 300 useful words and phrases. The phrasebook contains more than 1,200 words and phrases and an easy-to-understand pronunciation guide.